KEARIFAN LOKAL MASYARAKAT DI KABUPATEN KAUR PROVINSI BENGKULU - NFN Undri (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2018)
This paper focuses on the shape and influence of local wisdom of rural communities in Kaur Districtof Bengkulu Province. The communities in the area have local wisdom that still exist and have notchanged and even as a social buffer for conservation efforts and sustainability of natural resources,especially in the field of agriculture. This research uses historical research method. In historical researchmethods through four important stages: first heuristic, searching for and finding historical sources orcollecting resources, Secondly, criticism assesses whether authentic or not a source and how muchsource credibility. Third, the synthesis of facts obtained through source criticism or credibility of thesource, and fourth, the presentation of the results in written form. The result of this research is thatpeople in Kaur District of Bengkulu Province have local wisdom in agriculture called repung. Thecommunity provides land in every clan to be planted with food crops called repung. The form of localwisdom of the community in Kaur District can be divided into the first form, local wisdom in agriculture.Second, local wisdom in forest management. The influence of local wisdom in the life of the communityin the environment of society in Kaur, its influence can be divided into two that is positive and will bepreserved environmental sustainability and negative, that is environmental damage for the people ofKaur itself.